Implementasi Pasal 3 Huruf C Peraturan Bupati Jember Nomor 29 Tahun 2024 Tentang Percepatan Penurunan Stunting Terintegrasi Pada Ibu Hamil Di Kecamatan Kaliwates - Feri Aji; Icha Cahyaning Fitri (Empat Sembilan Publisher, 2026)
Despite national efforts to reduce stunting, Kaliwates District in Jember Regency presents a unique paradox where high stunting prevalence persists amidst adequate urban infrastructure. This study aims to analyze the implementation effectiveness of Article 3 Letter C of Jember Regent Regulation Number 29 of 2024, specifically regarding integrated interventions for pregnant women, and to identify the determinative factors behind its execution. Employing a juridical empirical method with a socio-legal approach, this research utilizes primary data obtained through in-depth interviews with pregnant women, health officials, and local government agencies, complemented by observations and legal documentation analysis. The findings reveal that the regulatory mandate for integrated services remains largely unfulfilled due to significant bureaucratic fragmentation and sectoral ego between agencies. A critical discovery is the phenomenon of administrative stunting, where rigid requirements for residency documents exclude vulnerable populations from accessing state sponsored nutrition programs. Furthermore, the implementation faces cultural resistance from elite urban communities who reject health interventions, viewing them as irrelevant to their social status. Consequently, the regulation has not been effective, creating a distinct gap between the written law and its practical application. The study concludes that structural rigidity and lack of officer legitimacy hinder the protection of constitutional health rights. These findings imply an urgent need for bureaucratic reform towards more adaptive governance, requiring policymakers to establish discretionary mechanisms that bypass administrative hurdles to ensure stunting eradication efforts are inclusive for all social strata.